PERBEDAAN TEKANAN DARAH PADA LANSIA PENDERITA HIPERTENSI SEBELUM DAN SESUDAH MELAKUKAN SENAM JANTUNG SEHAT DI POSYANDU LANSIA KECAMATAN PATRANG - Khofi Hadidi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2017)
Hypertension in the elderly is one of the disorders of the cardiovascular system caused by decreased elasticity of the arteries, the management of hypertension can do healthy heart exercises (Damayanti, 2014). The purpose of this study is to determine the differences in blood pressure in patients with hypertension before and after doing a healthy heart gymnastics in the elderly post Jember. This research method uses a pre-experimental design with one group pre-test and post-test design without using a control group with a population of 56 elderly. Sampling using simple random sampling technique with a sample of 40 elderly. Data collection instrument by measuring with the intervention of healthy heart exercises within 30 minutes for 4 times a week. After the data were collected, it was analyzed using the Wilcoxon Signed Ranks Test statistical test to get an Asymp Sig of 0.001. So it can be concluded that the p value of 0.001 means that there is a significant decrease in blood pressure in the elderly after healthy heart exercises. The conclusion in this study there are differences in blood pressure in patients with hypertension before and after doing a healthy heart gymnastics in the Elderly Posyandu Jember. Suggestions are expected to be used as an intervention for the management of hypertension in patients with hypertension